2023
DOI: 10.1039/d3ta00552f
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the electrochemical reaction mechanism of lithium-rich antiperovskite cathodes for lithium-ion batteries as exemplified by (Li2Fe)SeO

Abstract: We report outstanding properties of the antiperovskite cathode material (Li2Fe)SeO which for the first time was synthesized via direct ball-milling. The unique structured material displays excellent electrochemical cycling performance of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Specifically, the pair R 3 /O 3 in the low-voltage range which is attributed to the electrochemical activity of Fe 1–x S x increases drastically, while simultaneously, a significant decrease in the antiperovskite-associated oxidation processes (O 1 , O 2 , and O * ) is observed. Both the appearance of an extra feature as well as observed irreversibility is similar to what is found in (Li 2 Fe)SeO . We therefore conclude that during the anionic O* process, the antiperovskite phase decomposed and one or several iron sulfide phases are formed.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…Specifically, the pair R 3 /O 3 in the low-voltage range which is attributed to the electrochemical activity of Fe 1–x S x increases drastically, while simultaneously, a significant decrease in the antiperovskite-associated oxidation processes (O 1 , O 2 , and O * ) is observed. Both the appearance of an extra feature as well as observed irreversibility is similar to what is found in (Li 2 Fe)SeO . We therefore conclude that during the anionic O* process, the antiperovskite phase decomposed and one or several iron sulfide phases are formed.…”
Section: Resultssupporting
confidence: 80%
“…In our recent works on (Li 2 Fe)SeO, we have demonstrated the stabilizing effect of selenium as an anion in the antiperovskite structure for the electrochemical performance . We have also shown that the poor cycling stability in this system originates from the high-voltage electrochemical processes causing decomposition of the antiperovskite structure . When cutting off the decomposition reaction, the cycle stability is significantly improved (over 80% capacity retention after 100 cycles for (Li 2 Fe)SeO at 1 C in the voltage range from 1 to 2.5 V) .…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations